Implementation of the User Centered Design Method in the Android-Based Digital Financial Literacy Media Interactive Education Application (Case Study: Medan City MSMEs) - Aprilia, Annisa; Ikhwan, Ali (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
The existence of information and communication technology in this digital era has changed the way people interact with money and finance, especially with the emergence of internet developments such as mobile banking, e-commerce, and fintech which have brought great progress in the way people transact and manage finances. Financial transactions that are increasingly related to digital technology bring new benefits and challenges for UMKM business actors, the introduction of digital financial literacy in the context of UMKM is an important step in facing technology-driven business transformation. However, until now there are still many UMKM who still lack understanding of digital financial literacy. Lack of understanding about online transaction security, selection of appropriate services, and digital data management can hinder growth and potentially increase risks for UMKM later. This makes the need for digital financial literacy for UMKM even more real, this research will focus on helping to provide understanding to UMKM actors, especially Medan City about digital financial literacy through interactive educational applications by applying the User Centered Design Method for the development of their user interface, it is hoped that through this application UMKM actors in the city of Medan can optimize their understanding of digital financial literacy so that they can Take full advantage of financial technology to improve operational efficiency, grow businesses, and participate in the digital economy more effectively.